The extent to which the schools of the Education Administration in Al-Mukhawah Governorate applied to the school accreditation standards - Al-Ghamdi, Abdullah Khalaf Jamaan (Arab Journal for Sciences and Research Publishing, 2020)
The study aimed to identify the extent to which the schools of the Education Department in Al-Mukhawah Governorate applied the school accreditation standards and to determine the training needs of the schools of the Education Department in Al-Makhwa Governorate to support them in applying the school accreditation standards. Society and sample of the study: The research community consists of managers and managers of middle and secondary stage in Al-Makhwa Governorate, which number 63 managers and managers. The statistical package was used in the analysis and testing of hypotheses. The study concluded with a set of results, the most important of which was the acceptance of the hypothesis of the study that the areas used as indicators to measure the extent to which the schools of the Education Department In the application of standards. And that the field of effective school leadership of the most important indicators, which received the highest average arithmetic based on the response of principals and principals of schools and its impact on the extent of the application of the schools of the Department of Education in Al - The researcher also found that the interest and follow-up of the parents and the community got the lowest average arithmetic, which means that this field has a weak impact on the extent of application of the schools of the Department of Education in Al-Mukhawah to the standards of school accreditation.